2020
DOI: 10.3233/jnd-200551
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data from Nusinersen Treatment for Patients with Later-Onset Spinal Muscular Atrophy: A Single Center Experience

Abstract: Background Spinal muscular atrophy (SMA) is a motor neuron disease associated with progressive muscle weakness and motor disability. Objective This study aims to report the evaluation of nusinersen, an antisense oligonucleotide, on motor function in patients with SMA types 2 and 3. Methods This single-center retrospective observational study assessed nusinersen therapy outcomes, measured by HSMFSE or CHOP-INTEND scales, in patients with SMA types 2 and 3, compared to untreated patients, for at least 24 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…For children there is evidence from the placebo controlled CHERISH trial [12] and the open label extension (SHINE) [47] that treatment with nusinersen improves motor function. The improvement in the HFMSE in our study for type 3 patients was more pronounced than in type 2 patients and contradicts the findings of Darras et al [47] as well as real-life data by Szabo et al [48] and Mendonca et al [49]. However, our finding is in line with the data reported by Hagenacker et al [50] and Maggi et al [51], who showed a better nusinersen treatment response of adults with less severe forms of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…For children there is evidence from the placebo controlled CHERISH trial [12] and the open label extension (SHINE) [47] that treatment with nusinersen improves motor function. The improvement in the HFMSE in our study for type 3 patients was more pronounced than in type 2 patients and contradicts the findings of Darras et al [47] as well as real-life data by Szabo et al [48] and Mendonca et al [49]. However, our finding is in line with the data reported by Hagenacker et al [50] and Maggi et al [51], who showed a better nusinersen treatment response of adults with less severe forms of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the early real-world data have focused on type 1 infants enrolled in early access programs, [8][9][10] but in the last few years several studies have reported additional data in older children [11][12][13][14] and adults [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], covering the whole spectrum of SMA, from young infants with the most severe forms [30] to adults with a milder phenotype. The real-world data have expanded our knowledge on safety and efficacy of the drug in a much larger population of SMA patients than those reported in the pivotal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Functional improvement has also been reported in children and adult classically labeled as type 2 and 3 but the interpretation of the data and the comparison between different datasets is complicated by the differences in the cohorts studied and by the tools used to establish efficacy. The interpretation of the results is further complicated by the relative paucity of age specific reference data in untreated patients, especially in adult cohorts [26,[37][38][39][40][41][42][43][44][45][46]. The aim of this paper was to critically review the existing literature on motor function in type 2 and 3 patients treated with Nusinersen, trying to establish possible patterns of efficacy by subdividing the results according to SMA type, age (pediatric vs adults) and type of assessment.…”
Section: Introductionmentioning
confidence: 99%
“…There is a rapidly increasing number reporting efficacy of the drug in a real world setting. While most of the early real-world data focused on type 1 infants enrolled in early access programs, [37][38][39] there has been a rapidly increase in the number of patients reporting real world data in adults [40][41][42][43][44][45][46][47][48][49][50][51][52][53] and older children [54][55][56][57][58] covering the whole spectrum of SMA, from young infants with the severe neonatal onset forms to adults with milder phenotypes. The real-world data have expanded our knowledge on safety and efficacy of the drug in a much larger population of SMA patients than those reported in the pivotal studies.…”
Section: New Therapiesmentioning
confidence: 99%